Significant improvement of the self-protection capability of ultra-high temperature ceramic matrix composites. (15th August 2021) - Servadei, Francesca; Zoli, Luca; Vinci, Antonio; Galizia, Pietro; Sciti, Diletta
Highlights: Short term oxidation tests at 1500 °C and 1650 °C were carried out on UHTCMC. Less than 30 vol% of ZrB2 into SiC(O) matrix is able to impart a fast passivation. Oxidation resistance was affected by the distribution of ZrB2 into the SiC matrix. Abstract: The oxidation behaviour of Cf /ZrB2 -SiC with different fibre architectures, manufactured by slurry impregnation, polymer infiltration and mild pyrolysis, was investigated. Short term oxidation tests in air were performed for 1 min and 5 min at 1500 °C and 1650 °C in a bottom loading furnace. Microstructure, oxide scale thickness and composition were analysed by SEM/EDS/XRD. Results indicated that a good dispersion of ZrB2 particles in the polymer derived SiC(O) matrix promoted the formation of compact scales filling surface holes left by fibre oxidation. 20−30 vol% of ZrB2 in the material was found a good compromise between lightness and oxidation resistance.